Empowering Women in Islamic Rituals: A Participatory Approach to Barzanji Recitations in Bugis Pesantren - Muammar Bakry; Abdul Syatar; Arif Rahman Ramli; Sona Minasyan (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2025)
Barzanji recitations in Bugis pesantrens in Makassar have traditionally relegated women to passive roles, reflecting entrenched gender norms. This study aims to empower women to participate actively in Barzanji rituals at the Multidimensional Alfakhriyah Islamic Boarding School by implementing a gender‑sensitive Participatory Action Research (PAR) framework. Data collection included in‑depth interviews, focus group discussions, and field observations. The intervention comprised Barzanji sessions co‑designed with female santri and community leaders, featuring flexible timing and culturally adapted formats. Findings reveal that women’s participation increased from 12 % to 68 %, accompanied by enhanced spiritual understanding and a strengthened sense of ownership over the ritual. Participatory monitoring further reinforced women’s agency within religious spaces. These results demonstrate that gender‑responsive programs can effectively shift traditional norms and position women as active agents of change within Islamic ritual practice. This study contributes to gender and Islamic scholarship by presenting a scalable model suitable for other pesantrens. Future applications may include broader implementation across Sulawesi and longitudinal research to assess cultural transformation.